GROWTH OF NAUCLEA ORIENTALIS SPECIES OF YOUNG PLANTATION FOR BIG TIMBER PRODUCTION IN HOA BINH PROVINCE - Tho, Hoang Vu (Journal of Forestry Science and Technology, 2023)
The results of the growths and development of Nauclea orientalis species from the experimental planting model for big timber production in Hoa Binh province showed that, Nauclea orientalis trees have been adapted, growth quite well on the sites at the age of 16 months in Hoa Binh province. It is worth noting that, the model of Nauclea orientalis plantation had a high survival rate and healthy (93.5%), growths in diameter, height and average canopy diameter were 2.67 cm, 1.09 m, and 2.2 m respectively. Nauclea orientalis a native species has been performed the ability to develop branches suitably towards big timber production. The branchs of plantation are initially stable, shaped and capable of good growth and development stage. The results of the growth and development assessment from this experimental planting model are very important, not only providing valuable scientific information, but also a vivid practical basis demonstrating the ability planted and develop multi-use, and economically valuable Nauclea orientalis species, and add new varieties into the structure of forestry plant varieties for production forests in the direction of developing big timber forests in Hoa Binh province.